Clinical and ultrasound characteristics of the microcystic elongated and fragmented (MELF) pattern in endometrial cancer according to the International Endometrial Tumor Analysis (IETA) criteria. Issue 1 (7th January 2019) - Eriksson, Linda S E; Nastic, Denis; Frühauf, Filip; Fischerova, Daniela; Nemejcova, Kristyna; Bono, Francesca; Franchi, Dorella; Fruscio, Robert; Ghioni, Mariacristina; Haak, Lucia A; Hejda, Vaclav; Meskauskas, Raimundas; et al.
Abstract : Objectives: To describe sonographic features of the microcystic elongated and fragmented (MELF) pattern of myometrial invasion (MI) using the International Endometrial Tumor Analysis (IETA) criteria; to assess the effect of the MELF pattern on preoperative ultrasound evaluation of MI; and to determine the relationship of the MELF pattern to more advanced stage (≥ IB) and lymph node metastases in women with endometrioid endometrial cancer. Methods/materials: We included 850 women with endometrioid endometrial cancer from the prospective IETA study. Ultrasound experts performed all ultrasound examinations, according to the IETA protocol. Reference pathologists assessed the presence or absence of the MELF pattern. Sonographic features and accuracy of ultrasound assessment of MI were compared in cases with the presence and the absence of the MELF pattern. The MELF pattern was correlated to more advanced stage (≥IB) and lymph node metastases. Results: The MELF pattern was present in 197 (23.2%) women. On preoperative ultrasound imaging the endometrium was thicker (p = 0.031), more richly vascularized (p = 0.003) with the multiple multifocal vessel pattern (p < 0.001) and the assessment of adenomyosis was more often uncertain (p < 0.001). The presence or the absence of the MELF pattern did not affect the accuracy of the assessment of MI. The MELF pattern was associated with MI ≥ 50% (p < 0.001), cervical stromal invasion (p = 0.037), more advanced stage (≥ IB) (p < 0.001) and lymph node metastases (p = 0.011). Conclusions: Tumors with the MELF pattern were slightly larger, more richly vascularized with multiple multifocal vessels and assessment of adenomyosis was more uncertain on ultrasound imaging. The MELF pattern did not increase the risk of underestimating MI in preoperative ultrasound staging. Tumors with the MELF pattern were more than twice as likely to have more advanced stage (≥ IB) and lymph node metastases.